Community participation and food security in a developing context: a critical health psychology perspective - Milovanovic, Minja (My University, 2012)
The primary aim of the study was to critically analyse how concepts such as community and participation are represented in relation to food gardens against the back drop of corporate social initiatives and public private partnerships. Using a variety of data sources; interviews, and internet documents, this study looked at two case studies of community food gardens in separate schools in Gauteng, South Africa. Both schools were part of a food garden intervention implemented by two separate organisations. The collected data allowed for a comprehensive analysis of the concepts that underpin food security interventions. The data was analysed using thematic content analysis and drew on critical realism and recent writing in critical health psychology. The results showed that the main topics under discussion include challenging notions of community and participation, empowerment, individualism, education and partnerships. Development approaches draw on these concepts to promote community based interventions that effectively position individual members as responsible for their community’s food insecurity. Such concepts reflect a psychologised way of thinking about health which has become prevalent in development. Critically exploring these concepts highlights how psychologising food insecurity has the effect of ignoring the structural cause of the problem.
M.A. University of the Witwatersrand, Faculty of Humanities (Research Psychology), 2012